Religion in the media: A look at recent books and Web sites (Knight Ridder Tribune News Service, 2004)
This is a mixed collection of Sabbath songs. Lovers of tradition can celebrate with tunes such as "Mah Tovu" sung to a Chabad melody, and "Yismechu Hashamayim," put to a Hassidic melody. Those who prefer contemporary songs will appreciate [Susan Colin]'s interpretation of Debbie Friedman's "Mi Shebeirach" and "Sh'ma/V'ahavta." [Charles Freeman] writes about the history of ideas and their connection to power. He describes how the attitudes and methods of the Greek philosophers were displaced by those of Christian theologians. This long, well-written book demonstrates that what arose to replace reason was not faith, as the subtitle asserts, but rather authority. It was, Freeman writes, the closed and controlling stance of the Christian church that replaced the open and exploratory tradition of the Greek academy. The site also throws in Islam, Christianity and Judaism in the mix, and, interestingly, the list of links under these categories are fairly conservative in viewpoint. Under Judaism, you'll find sites on keeping a kosher kitchen; under Christianity, there are conservative sites such as Handmaidens 4 Christ, an online women's fellowship.